A pilot randomized controlled trial on the impact of text messaging check-ins and a web-based asthma action plan versus a written action plan on asthma exacerbations. (3rd August 2019) - Poureslami, Iraj; Shum, Jessica; Lester, Richard T.; Tavakoli, Hamid; Dorscheid, Delbert R.; FitzGerald, J. Mark
Abstract: Objective : We compared electronic asthma action plans (eAAP) supported by automated text messaging service (SMS) with written asthma action plans (AAP) on assessing acceptability and asthma control improvement. We hypothesized that the patients in eAAP group would have more improvements in their quality of life, asthma control and decreased asthma exacerbations. Methods : Patients with physician-diagnosed asthma having at least one asthma exacerbation in the previous 12 months were recruited. Participants received individualized action plans and were randomly assigned into either the intervention (eAAP) or control (AAP) group. Intervention participants received weekly SMS, triggering assessment of asthma control and viewing their eAAP. We assessed applicability of Telehealth platform on asthma exacerbations, asthma control, and quality of life over a 12-month period. Results : 106 patients were enrolled (eAAP = 52, AAP = 54). The cumulative response rate to all weekly SMS check-ins was 68.4%. Overall, 28% of patients checked into their eAAP during the intervention period. There were fewer exacerbations in the eAAP group (18%) compared to the AAP group (RR = 0.82 [95%CI 0.49, 1.36]), (P = 0.44). The mean scores for asthma control and quality of life were higher in the eAAP group compared to the AAP group by 4% (RR = 1.04 [95%CI 0.83, 1.30]), (P =  0.73) and 5.5% (RR = 1.06 [95%CI 0.87, 1.28]), (P = 0.59), respectively, but were not statistically significant. Conclusions : We demonstrated that the eAAP presented improved asthma control outcomes, but as expected the sample size was inadequate to show a significant difference, but based on this pilot study we plan a larger appropriately powered randomized controlled trial (RCT).